Seyyid Ahmed Şehid’in ilâhi aşk ve seyrü sülûk anlayışı - Butt, Hafiz Ali Ahmad (My University, 2022)
SEYYİD AHMED ŞEHİD’İN İLÂHİ AŞK VE SEYRÜ SÜLÛK ANLAYIŞI Bu çalışma Seyyid Ahmed Şehid'in (ö.1831) hayatını ve tasavvufi öğretilerini incelemeyi amaçlamaktadır. Çalışmamız özellikle Seyyid'in İlâhi Aşk anlayışına ve onun Sülûk (manevi yolculuk) hakkındaki öğretilerine odaklanmaktadır. Bugüne kadar Seyyid Ahmed’in “Cihad hareketi” kapsamlı bir şekilde incelenmiş, ancak “Sufi öğretileri” yeterince araştırılmamıştır. Dolayısıyla bu çalışma, onun “İlahi Aşk” ve “Sülûk” hakkındaki tasavvufi fikirlerini incelemeye yönelik akademik bir girişimdir. Çalışmamız, Seyyid Ahmed’in hayatının önemli evrelerini araştırmakta ve kendisinin aile geçmişini ve Hint Yarımadası'nın önde gelen alimleriyle olan entelektüel bağlarını incelemeyi amaçlamaktadır. Seyyid Ahmed'in o dönemde ilim merkezi olan Delhi'de kalışı da araştırmamız çerçevesinde kapsamlı bir şekilde incelenmiştir. Ayrıca çalışmamız aynı zamanda Seyyid Ahmed'in aktivizmini de ele almakta ve kendisinin “Davet faaliyetlerine” bir nebze de olsa ışık tutmaktadır. Tasavvufun ayrılmaz bir parçası olarak kabul edilen İlâhi Aşk, Allah ile insan arasındaki bir aşk ilişkisini ifade eder. Klasik ve modern tasavvuf âlimlerinin bu öğretinin farklı manevî ve felsefî boyutlarını geniş bir şekilde izah ettikleri bilinmektedir. Bu nedenle, bu çalışma Seyyid Ahmed'in İlâhi Aşk hakkındaki görüşlerini araştırmayı, İlâhî Aşkın “Ḥubb-i İşkî” ve “Ḥubb-i İmânî” olarak sınıflandırılmasını ve bu iki İlâhî Aşk türünün temel özelliklerini araştırmayı amaçlamaktadır. Bu araştırma aynı zamanda Seyyid Ahmed'in Sülûk'un iki ana yola, yani “Rāh-i Wilāyah (velilik yolu)” ve “Rāh-i Nubuwwah'a (nübüvvet yolu)” ayrıldığı ve bunları İlahi Aşk doktrini ile ilişkilendirdiğine de incelemektedir. Rāh-i Wilāyah ve Rāh-i Nubuwwah'a göre Sulûk'un tüm süreçleri ve farklı evreleri de araştırmamızda derinlemesine incelenmiştir.

SAYYID AHMAD SHAHEED: HIS UNDERSTANDING OF DIVINE LOVE AND SULŪK This research aims to study life and Sufi teachings of Sayyid Ahmad Shaheed (d.1831). Sayyid has been studied for his Jihād movement, but his Sufi teachings remained under researched. Therefore, this study is an academic attempt to study his Sufi ideas about Divine Love and Sulūk. (Spiritual wayfaring) This study investigates important phases of Sayyid’s life and aims to study his family background and intellectual links with prominent scholars of Indian subcontinent. Sayyid’s stay in Delhi which was center of knowledge and learning in 18th century AD, has also been extensively studied in this research. Moreover, this study also discusses Sayyid’s activism and sheds some light on his Da‘wah activities. Divine Love which is considered to be an integral part of Sufism refers to a relationship of love between God and human beings. It is commonly known that classical and modern Sufi scholars have broadly explained different spiritual and philosophical dimensions of this doctrine. Likewise, extensive discussion on Divine Love and its relationship with Sulūk has been detected in Sayyid’s Sufi thought. Thus, this study is devoted to understand his views about Divine Love and to study his categorization of Divine Love into Ḥubb-i ‘Ishqī and Ḥubb-i Īmānī. In addition, the main features of these two types of Divine Love and distinction between them are also within the scope of this research. This research also studies Sayyid’s teachings about Sulūk as he divides it into two main paths i.e., Rāh-i Wilāyah (The saintly path) and Rāh-i Nubuwwah (path of prophethood) and links them to the doctrine of Divine Love. All the spiritual activities and different phases of Sulūk according to Rāh-i Wilāyah and Rāh-i Nubuwwah have also been profoundly studied in this research.
Keywords: Bid’ah; Bid‘at Sufism; Divine Love; Hindistan; Indian subcontinent; Islam; İlâhi Aşk; İslam; Seyrü Sülûk; Sufi orders; Sulūk; Tarikatlar